Characteristics of aquaporin 1, 3, and 5 expression during early murine salivary gland development. Issue 3 (19th October 2020) - de Paula, Fernanda; Tucker, Abigail S.; Teshima, Tathyane Harumi N.; de Souza, Milena Monteiro; Coutinho‐Camillo, Cláudia Malheiros; Nico, Marcello Menta S.; Lourenço, Silvia Vanessa
Abstract: Aquaporins (AQPs) are essential to coordinate the transit of water and ions through the cell membrane. In salivary glands (SGs), AQPs have been associated with saliva formation, facilitating water absorption through the epithelium during the formation of hypotonic saliva, which is then secreted into the oral cavity. Different members of the AQP family have been suggested to play distinct roles during embryonic development, highlighted by their specific expression patterns. Here, we have investigated the expression patterns of AQP‐1, AQP‐3 and AQP‐5 by immunofluorescence at key stages of salivary gland development, utilising cultured mouse embryonic submandibular (SMG) and sublingual (SLG) glands. The expression of AQPs was compared to a mitotic marker, phospho‐histone 3 (PH3), a myoepithelial marker, smooth muscle actin (SMA), and a vascular marker, CD31. Qualitative analysis revealed that AQP‐1 and AQP‐3 were primarily expressed during the earlier phases of SG morphogenesis and were associated with cells undergoing mitotic processes (PH3‐positive). AQP‐5, in contrast, was not associated to mitotic figures, but was predominantly expressed during late stages of SG morphogenesis. Our results highlight that AQPs are expressed from early stages of SG morphogenesis and exhibit complimentary expression patterns that may contribute to the morphogenesis of salivary glands. Abstract : AQP‐1 in mouse developing salivary glandsA: AQP‐1 expression in basal cell membranes (green ‐ A') co‐expressed with PH3 nuclear staining (red ‐ A''). B: At E14.5: AQP‐1 and PH3, showing expression in the ductal and acinar epithelium. C and D: Salivary gland at E16.5, showing condensed mitotic nuclei (blue) colocalised with AQP‐1 in several acinar cells and ductal epithelia.